The learning challenges faced by UiTM students in Covid-19 post pandemic / Mohamad Shafiei Ayub … [et al.] - Ayub, Mohamad Shafiei; Abdul Kadir, Nor Adina; Md Shah, Nursyaidatul Kamar; Abd Rahman, Mohd Farhan (Academy of Contemporary Islamic Studies (ACIS), 2021)
In late 2019, the world was shaken by the outbreak of an unprecedented infectious epidemic namely Coronavirus Disease or Covid-19. Due to this, all Malaysians are required to comply and adopt to the new norms based on the guidelines issued by the Ministry of Health of Malaysia (MOH). The entire national system is affected by this concerning development and the structure of Teaching and Learning (PdP) in the field of education is no exception. The structure of PdP, previously conducted conventionally or face-to-face, centered on educators and students directly, has changed its implementation to virtual and digital using the methods of Teaching and Learning at Home (PdPR) or Home-Based Learning (HBL) to ensure continuity in students’ learning. Thus, this study aims to identify the main obstacles faced by UiTM Melaka Branch students in their learning process as they dealt with COVID-19 and the challenges that comes with the pandemic. This qualitative study applies library methods, observation, interviews and analysis methods. The study was conducted by administering a questionnaire to several students of UiTM Melaka Branch to obtain accurate feedback. The findings of the study showed that students’ challenges are limited access to communication technology, changes in the reading and reference material search system, spending too much time in front of the screen, changes in students' daily lifestyles and external interference while completing their online tasks.